Redescription of Microprosthema semilaeve (von Martens, 1872) (Decapoda: Stenopodidea: Spongicolidae) and description of a new species of Microprosthema from Dry Tortugas, Florida - Goy, Joseph W.; Martin, Joel W. (Zootaxa, 2013)
Microprosthema semilaeve, a fairly common spongicolid shrimp of reefal habitats in the Western Atlantic and Caribbean is redescribed and figured based on type material and an additional 78 specimens from the majority of its known zoogeographical range. It is distinguished from the Indo-Pacific species of M. validum and an undescribed species of Microprosthema with which it has been confused in the literature by a number of morphological characters. A new species of Microprosthema from deeper waters off the Dry Tortugas and closely related to M. inornatum Manning & Chace, 1990, is described and illustrated. Microprosthema jareckii Martin, 2002 is synonymized with M. manningi Goy & Felder, 1988. A key to the Western Atlantic species of Microprosthema is presented.